Reconstruction and Functional Annotation of P311 Protein–Protein Interaction Network Reveals Its New Functions - Wang, Song; Zhang, Xiaorong; Hao, Fen; Li, Yan; Sun, Chao; Zhan, Rixing; Wang, Ying; He, Weifeng; Li, Haisheng; Luo, Gaoxing (Frontiers in Genetics, 2019)
P311 is a highly conserved multifunctional protein. However, it does not belong to any established family of proteins, and its biological function has not been entirely determined. This study aimed to reveal the unknown molecular and cellular function of P311. OCG (Overlapping Cluster Generator) is a clustering method to partition a protein-protein network into overlapping clusters. Multifunctional proteins are at the intersection of relevant clusters. DAVID is an analytic tool to extract biological meaning from large protein list. Here we presented OD2(OCG+DAVID+2 human PPI datasets), a novel strategy to increase the likelihood to identify biological functions most pertinent to the multifunctional proteins. The principle of OD2 was that OCG prepared the protein lists from multifunctional protein relevant overlapping clusters for functional enrichment analysis by DAVID and the similar functional enrichments, which occurred simultaneously when analyzing two human PPI datasets, were supposed to be the predicted functions. By applying OD2 to 2 reconstructed human PPI datasets, we supposed the function of P311 in inflammatory responses, cell proliferation and coagulation, which were confirmed by the following biological experiments. Collectively, our study preliminarily found that P311 could play a role in inflammatory response, cell proliferation and coagulation. Further studies are required to validate and elucidate the underlying mechanism.